2009
DOI: 10.1097/fjc.0b013e3181a0ce8b
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Statin Therapy and Tendon Rupture: A Case-Control Study

Abstract: Although case reports of a possible association between statin therapy and tendon rupture have been published, no analytical studies exploring this relationship have been reported. We conducted a case-control study using the electronic medical records at Michigan State University from 2002 to 2007 to assess whether statin use is a risk factor for tendon rupture. We compared exposure to statins in 93 cases of tendon rupture with similar exposure in 279 sex- and age-matched controls. Exposure to statins was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…10,11 The extent of this risk and the influence of gender is not clear. 12 Many of these risk factors for shoulder problems were present in a significant proportion of the study group, and we observed a high rate of shoulder pain despite the predominantly male gender of the subjects. The sample size was likely too small to detect statistically significant relationships between shoulder pain and some of these risk factors, despite the high prevalence of statin use (58%), and diabetes (50%).…”
Section: Discussionmentioning
confidence: 54%
“…10,11 The extent of this risk and the influence of gender is not clear. 12 Many of these risk factors for shoulder problems were present in a significant proportion of the study group, and we observed a high rate of shoulder pain despite the predominantly male gender of the subjects. The sample size was likely too small to detect statistically significant relationships between shoulder pain and some of these risk factors, despite the high prevalence of statin use (58%), and diabetes (50%).…”
Section: Discussionmentioning
confidence: 54%
“…Results between studies, however, were mixed with two finding no significant association between diabetes and tendinopathy whereas three identified a positive association. Three of these studies reviewed large medical databases15 48 50 and two sampled cohorts of working populations47 57 but subgrouping in this way did not correspond to studies that reported significant associations.…”
Section: Resultsmentioning
confidence: 99%
“…Rosuvastatin and atorvastatin have been more frequently linked to side effects than other statins [2, 7, 8], while simvastatin gives rise to mixed outcomes [6, 7, 9]. Two retrospective studies indicate that simvastatin might have a protective role against tendinopathy, especially in patients suffering from severe hyperlipidemia [6, 7, 9] while another study indicates that simvastatin treatment is linked to tendon complications [8]. …”
Section: Introductionmentioning
confidence: 99%